TINJAUAN AL-QUR’AN TERHADAP GODAAN IBLIS DAN SETAN MENURUT HAMKA DALAM TAFSIR AL-AZHAR - Heryadi Heryadi (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2017)
The Qur'an as the main source of Islamic teachings clearly states that believing in the unseen is a characteristic of a believer. Hamka in Tafsir Al-Azhar states that, faith to the unseen is the basic belief in Islam. Satan as the main enemy of man constantly directs temptations to prevent man from God's straight path with various means of aberrations. Taking into account the interpretation of Hamka in the Al-Azhar Tafsir associated with verses that speak of Satan, is closely related to Satan. Therefore, a special study is needed to examine: The concept of Satan and Satan according to Hamka. And what are the ways of Satan and Satan in seducing men according to Hamka in Tafsir Al-Azhar ?. Because the discussion is the book of interpretation of the approach to the problem is the science of interpretation with a theoretical basis that is: Tafsir type, style of interpretation and methods of interpretation. The method used in this research is maudhu'i method. That is the method of interpretation that seeks to answer the Qur'an about the problem with thematic way. From the research that has been done can be concluded that: According to Hamka Satan is from the group of disobedient Jin to Allah swt. Satan is more than anything that is evil that plunges a person in a danger, both danger in the world and danger in the afterlife. Satan can be a negative passion that stimulates a person to behave evil and deviate from the truth. As for the manner and kind of temptation of Satan or Satan's many and varied tricks, among them, by derailing man, being deceived by far-reaching apostasy, whispering evil thoughts to deviate from the way of Allah swt. The straight and the other.